Management and Empowerment of zakat National Amil Zakat Agency of Jambi, city in Supporting Community Microeconomic Growth in the Islamic Economic Perspective) - Niska Zanita (Dinasti Publisher, 2022)
During to supporting Community Microeconomic Growth in the Islamic Economic Perspective). The activities of collecting, distributing and empowering zakat funds which are the core of the activities of zakat management organizations are still a problem that occurs in Baznas Jambi City. This study aims to determine how the management and Empowerment of Zakat funds carried out by Baznas Jambi City in improving the mustahiq economy. This research is a qualitative research with methods of collection and observation, intervews, and documentation.This research produces four conclusions, are: 1) the concept of implementing zakat management and empowerment by the Jambi City National Amil Zakat Agency in Supporting the mocroeconomic growth of society in the perspective of Islamic economics, Zakat has benefits for realizing the goals of broader Islamic social development.2) the zakat empowerment model carried out consists of consumptive zakat and productive zakat. Consumptive zakat is distibuted in the form of cash and food packages. Meanwhile, productive zakat is distributed in the form of business capital, business equipment, assistance for repairing business premises, training and assistance. However, in terms of economic improvement, it has not have a significant improvement, it has not have a significant impact and the are no report on business development from zakat recipients to Baznaz. 3). The factors that cause the low collection of zakat in Baznas Jambi City are the low public awareness in distributing zakat in Baznas. The ability in limitations of human resources in zakat management, as well as the lack of government support for zakat management institutions.The problems faced by the Jambi City Baznas in utilizing zakat are first, the collection of zakat funds has not been optimal so that it has an impact on the limited number of mustahiq and zakat funds received by mustahiq. Second. The limitations of human resources in socializing and utilizing zakat so that it has not been able to reach all are as in Jambi City they face.